1997
DOI: 10.1046/j.1365-2893.1997.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver targeting of antiviral nucleoside analogues through the asialoglycoprotein receptor

Abstract: In order to reduce the extrahepatic side-effects of antiviral nucleoside analogues in the treatment of chronic viral hepatitis, these drugs are conjugated with galactosyl-terminating macromolecules. The conjugates selectively enter hepatocytes after interaction of the carrier galactose residues with the asialoglycoprotein receptor present in large amounts and high affinity only on these cells. Within hepatocytes the conjugates are delivered to lysosomes where enzymes split the bond between the carrier and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 53 publications
(10 reference statements)
0
30
0
Order By: Relevance
“…Fiume et al reported on the conjugation of the antiviral analogue adenine arabinoside monophosphate (ara-AMP) to lactosaminated human serum albumin (L-HSA) (65). Clinical assays indicated that the administration of the prodrug to HBV-infected patients for 28 days leads to an antiviral activity similar to that of the free drug, though without any clinical adverse effect such as neurotoxicity.…”
Section: Drug Delivery and Targeting Strategies And Novel Anti-hbv Drmentioning
confidence: 99%
“…Fiume et al reported on the conjugation of the antiviral analogue adenine arabinoside monophosphate (ara-AMP) to lactosaminated human serum albumin (L-HSA) (65). Clinical assays indicated that the administration of the prodrug to HBV-infected patients for 28 days leads to an antiviral activity similar to that of the free drug, though without any clinical adverse effect such as neurotoxicity.…”
Section: Drug Delivery and Targeting Strategies And Novel Anti-hbv Drmentioning
confidence: 99%
“…Neoglycoproteins [9,39] have been used to target antiviral drugs [40], cytotoxic drugs [41] or macrophage acti- Starting with lactose, R stands for a b-galactopyranosyl residue, NH-P stands for one of the amines of the polymer P. In A, the glucose has been reduced into a pentahydroxy-hexylamine, while in B and C the glucose residue is preserved.…”
Section: Glycosylated Polylysinesmentioning
confidence: 99%
“…ASGP-R binds and internalizes a broad range of molecules exposing galactose or N-acetyl-galactosamine residues. Following internalization the fate of ligand is lysosomal degradation (Morell et al, 1968;Geffen and Spiess, 1992).Taking advantage of this receptor a chemotherapeutic approach has been developed to reduce the extrahepatic side-effects of nucleoside analogues (NAs) used in chronic viral hepatitis (Fiume et al, 1979(Fiume et al, , 1997 Torriani et al, 1996). These drugs are coupled to galactosyl-terminating peptides.…”
mentioning
confidence: 99%
“…Taking advantage of this receptor a chemotherapeutic approach has been developed to reduce the extrahepatic side-effects of nucleoside analogues (NAs) used in chronic viral hepatitis (Fiume et al, 1979(Fiume et al, , 1997Torriani et al, 1996). These drugs are coupled to galactosyl-terminating peptides.…”
mentioning
confidence: 99%